Haematotoxicity of Cypermethrin (25% EC) to white carp (Cirrhinus mrigala) - Neelima P; Govinda Rao K; Krishna Ch; Sunanda M; Chandra Sekhara Rao J (International Journal of Life Sciences, 2016)
Cyperkill 25%EC is a synthetic pyrethroid pesticide widely used in Guntur district for pest control in agri ventures due to its effective control against different pest species in a definitive and constant way with low cost. Its presence in freshwater environs is very common in this area. Contamination of aquatic ecosystems with this toxicant affects all groups of aquatic fauna including fish which are non target biota. A static-renewal bioassay was conducted to assess the acute and sublethal toxicity of cypermethrin on some haematological parameters of white carp (Cirrhinus mrigala). Juveniles of experimental fish were exposed for lethal (96 h LC50 i.e. 4.23μg/L) and sublethal (1/10th of 96 h LC50 i.e. 0.423μg/L for 5, 10 and 15 days) concentrations of cypermethrin. Decreased tendency at both lethal and sublethal concentrations was evident in RBC count, Hb content and PCV. At the same time an increasing trend in WBC count and MCHC at sublethal and decreasing trend at lethal concentration. MCV and MCH values were elevated at both lethal and sublethal concentrations. Toxicity derived alterations observed in haematological indices during this study led to a conclusion that the cypermethrin has detrimental effect on the test fish and its presence in an aquatic environment may severely threaten the health of the ecosystem and its living component.